Bioinformatics-based study on prokaryotic, archaeal and eukaryotic nucleic acid-binding proteins for identification of low-complexity and intrinsically disordered regions. Issue 1 (2nd January 2016) - Yadav, Birendra Singh; Singh, Swati; Kumar, Prashant; Mathur, Devika; Meena, Raj Kumar; Agrawal, Rishij Kumar; Mani, Ashutosh
ABSTRACT: Intrinsically disordered regions (IDRs) and low-complexity regions (LCRs) in transcription factors (TFs) are known to be key players in various cellular functions. Conformational flexibility of these regions allows them to recognize and interact with a large number of molecules. Previous studies show that certain TFs which are related to environmental response are significantly enriched in IDRs and LCRs. It has been proposed that all organisms in response to environmental conditions use these IDRs and LCRs for introducing versatility in the interactions in biological processes to quickly adapt and respond to challenging environmental conditions. A comparative study has been conducted on these regions to measure the average abundance of LCRs and IDRs in different types of TFs. In this project we have identified the IDRs and LCRs in prokaryotic, eukaryotic and archaeal TFs by using bioinformatics and compared them for average density of IDRs and LCRs.